2010
DOI: 10.1051/0004-6361/200913729
|View full text |Cite
|
Sign up to set email alerts
|

Giant pulses from the Crab pulsar

Abstract: The Crab pulsar is well-known for its anomalous giant radio pulse emission. Past studies have concentrated only on the very bright pulses or were insensitive to the faint end of the giant pulse luminosity distribution. With our new instrumentation offering a large bandwidth and high time resolution combined with the narrow radio beam of the Westerbork Synthesis Radio Telescope (WSRT), we seek to probe the weak giant pulse emission regime. The WSRT was used in a phased array mode, resolving a large fraction of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
112
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(142 citation statements)
references
References 39 publications
24
112
6
Order By: Relevance
“…Some of them, however, show variations in amplitude as a function of frequency, which have been seen before (e.g., Karuppusamy et al 2010). We also see variations in amplitude between days, which is likely due to refractive interstellar scintillation (RISS), which can affect the strength of pulses on a timescale of days.…”
Section: Radio Observationssupporting
confidence: 58%
See 1 more Smart Citation
“…Some of them, however, show variations in amplitude as a function of frequency, which have been seen before (e.g., Karuppusamy et al 2010). We also see variations in amplitude between days, which is likely due to refractive interstellar scintillation (RISS), which can affect the strength of pulses on a timescale of days.…”
Section: Radio Observationssupporting
confidence: 58%
“…In our data, ∼87% of detected GPs were at the phase of the MP, while the other ∼13% were at the phase of the IP. Only 5% of GPs detected by Cordes et al (2004) at 1.2 GHz were at the phase of the IP, but Karuppusamy et al (2010) found that ∼12% of GPs detected at 1.4 GHz were IP GPs. For detected pulses that show up out of phase with the MP and IP, the frequency versus time plots are checked by eye to see if they show the proper quadratic frequency sweep for a DM of 56.8 pc cm −3 .…”
Section: Radio Observationsmentioning
confidence: 89%
“…We can also compare the slopes estimated at other frequencies. Karuppusamy et al (2010) report slopes of −3.0 and −2.8 at 1400 MHz for the main-and interpulses flux distributions, respectively. Similarly, Lundgren et al (1995) find a value of −3.3 at 800 MHz and Cordes et al (2004) report ≈−2.3 at 430 MHz and noted that the slope increased with frequency.…”
Section: Giant Pulse Statisticsmentioning
confidence: 91%
“…3 of Karuppusamy et al (2010). In short, the increase in T sys due to the Crab nebula was multiplied by a factor that is a function of radio frequency and the hour-angle of the Crab pulsar.…”
Section: Flux Calibrationmentioning
confidence: 99%
See 1 more Smart Citation